Opportunities and limitations of CT - assessment of neoadjuvant chemoradiation therapy of gastric cancer - T. A. Agababyan; N. K. Silanteva; V. Yu. Skoropad; S. A. Ivanov; A. D. Kaprin; Yu. A. Komin; A. Yu. Usacheva; D. D. Kudryavtsev (Исследования и практика в медицине)
Purpose of the study. To study the possibilities of computed tomography in assessing the immediate antitumor effect of preoperative prolonged chemoradiotherapy in patients with primary and recurrent gastric cancer.Materials and methods. Twenty nine consecutive patients with locally advanced and recurrence cancer of the stomach, who underwent CT for the assessment of tumor response of neoadjuvant chemoradiotherapy of gastric cancer, were prospectively enrolled in our study. All patients underwent the method of neoadjuvant chemoradiotherapy developed in our Center. MDCT was performed before chemo-radiotherapy and 3.5-5 weeks after its completion.Results. Among the patients with primary gastric cancer (n = 24) it is necessary to explore three aspects: symptoms of the tumor response, tumor size and structure.CT allowed very clearly follow the symptoms of the tumor response. On the prechemoradiotherapy CT, two tumors were diagnosed as cT0-3 stage, 22 tumors as cT4. After the chemoradiotherapy 13 tumors were diagnosed as cT0-3 stage, 11 tumors as cT4 stage (x2=11,6; p<0.01).We analyzed the quantitative parameters, which included the maximal wall thickness perpendicular to the gastric lumen and the maximal square of the tumor. The maximal wall thickness (p<0.001) and the maximal area of the tumor (p<0.001) decreased significantly in postchemoradiotherapy scans compared to the baseline.CT texture analysis after the completion of radiochemotherapy showed that the primary tumors became more homogenous with the multilayer pattern, especially in the peripheral portion of the residual tumor, a marked enhancement of the mucosal layer of the stomach in 17 of 24 patients (71%) in the arterial phase and in 20 of 24 patients (83%) in the portal and/or venous phases.Accurate measurement of the tumor before and after the therapy allowed the evaluating the response to therapy by RECIST 1.1 criteria. Among the patients with recurrent gastric cancer partial response was observed in 2, stable disease in 2, progressive disease in 1.Conclusion. CT significantly improves capability of neoadjuvant therapy response evaluation in patients with gastric cancer. It is necessary to explore three aspects: symptoms of the tumor response, tumor size and attenuation.